Morphological details of microorganisms revealed by RCH-microscopy at high magnification--a ready-to-use adaptation of a light microscope - Zizka, Z; Hostounský, Z; Kálalová, S (Folia microbiologica, 2001)
RCH-microscopy (Relief Contrast after Hostounský) is a new method of optical microscopy in transmitted light developed with Lambda Ltd., Prague. This method was used to study bacteria, fungi including yeasts and algae at high magnification. The equipment provides a three-dimensional image of high contrast and resolution. The results of these microscopic observations can be used for both morphological (taxonomical) and ecological studies of microorganisms.
Keywords: Image Enhancement; Light; Fungi; světlo; mikroskopie; vylepšení obrazu; Bacteria; houby; Microscopy; Eukaryota